The influence of resin infiltration system on enamel microhardness and surface roughness: An in vitro study - Nadia Malek Taher; Haifa Abdulrahman Alkhamis; Sarah Mesha'l Dowaidi (Elsevier, 2012)
Objective: To investigate the effect of a resin infiltrant on the surface microhardness and roughness of healthy enamel and, as a subsidiary aim, to compare it with a fissure sealant. Materials and methods: Twenty freshly extracted premolars were used. Sound enamel surfaces were treated with a resin infiltrant (Icon) or fissure sealant (Seal-Rite). The average roughness (Ra, μm) of the specimens was measured with a profilometer (Surtronic 10 Tylor Hobson). Surface hardness was determined by utilizing Vicker's surface hardness (VHN) with a Micromet II Microhardness tester. Each specimen acted as its own control. Data were analyzed with 2-way analysis of variance (ANOVA), and mean values were compared with independent t-test. All analyses were performed with the SPSS program version 16 (USA). Differences with a P-value of ⩽0.05 were considered statistically significant. Results: Comparison of enamel surfaces before and after application of resin infiltrant revealed no significant differences in surface hardness; however, enamel surfaces treated by infiltrant showed significantly higher VHN (244.0 ± 79.8) values than those treated with fissure sealant (37.5 ± 14.2). Surface roughness did not differ before and after application of either material to sound enamel. Enamel surfaces treated with fissure sealant (5.3 ± 1.4) were significantly smoother than those treated with infiltrant (6.9 ± 2.0). Conclusion: Within the limitations of the study, the results showed that enamels treated with the resin infiltrant showed approximately the same microhardness and surface roughness as sound enamel, indicating that this material might be suitable for the treatment of enamel subsurface lesions. Keywords: Icon, Surface roughness, Surface hardness, Resin infiltration, Fissure sealant, Seal-Rite